Different Reactive Oxygen Species Scavenging Properties of Flavonoids Determine Their Abilities to Extend the Shelf Life of Tomato. Issue 3 (16th June 2015) - Zhang, Yang; De Stefano, Rosalba; Robine, Marie; Butelli, Eugenio; Bulling, Katharina; Hill, Lionel; Rejzek, Martin; Martin, Cathie; Schoonbeek, Henk-jan
Abstract : The structures of flavonoids influence their ROS-scavenging abilities and extend the shelf life of tomato fruit through effects on both overripening and susceptibility to Botrytis cinerea. Abstract: The shelf life of tomato ( Solanum lycopersicum ) fruit is determined by the processes of overripening and susceptibility to pathogens. Postharvest shelf life is one of the most important traits for commercially grown tomatoes. We compared the shelf life of tomato fruit that accumulate different flavonoids and found that delayed overripening is associated with increased total antioxidant capacity caused by the accumulation of flavonoids in the fruit. However, reduced susceptibility to Botrytis cinerea, a major postharvest fungal pathogen of tomato, is conferred by specific flavonoids only. We demonstrate an association between flavonoid structure, selective scavenging ability for different free radicals, and reduced susceptibility to B. cinerea . Our study provides mechanistic insight into how flavonoids influence the shelf life, information that could be used to improve the shelf life of tomato and, potentially, other soft fruit.